Chinese Society of Clinical Oncology (CSCO): Clinical guidelines for the diagnosis and treatment of pancreatic cancer - Jiujie Cui; Feng Jiao; Qi Li; Zheng Wang; Deliang Fu; Jun Liang; Houjie Liang; Tingyi Xia; Tao Zhang; Yang Zhang; Guanghai Dai; Zhihong Zhang; et al. (Journal of the National Cancer Center, 2022)
Pancreatic cancer is one of the leading causes of cancer-related mortality in both developed and developing countries. The incidence of pancreatic cancer in China accounts for about a quater of the global incidence, and the epidemiological characteristics and therapeutic strategies differ due to social, economic, cultural, environmental, and public health factors. Non-domestic guidelines do not reflect the clinicopathologic characteristics and treatment patterns of Chinese patients. Thus, in 2018, the Chinese Society of Clinical Oncology (CSCO) organized a panel of senior experts from all sub-specialties within the field of pancreatic oncology to compile the Chinese guidelines for the diagnosis and treatment of pancreatic cancer. The guidelines were made based on both the Western and Eastern clinical evidence and updated every one or two years. The experts made consensus judgments and classified evidence-based recommendations into various grades according to the regional differences, the accessibility of diagnostic and treatment resources, and health economic indexes in China. Here we present the latest version of the guidelines, which covers the diagnosis, treatment, and follow-up of pancreatic cancer. The guidelines might standardize the diagnosis and treatment of pancreatic cancer in China and will encourage oncologists to design and conduct more clinical trials about pancreatic cancer.